Memberdayakan Desa Melalui Pariwisata Berbasis BUMDES - Abdur Rozaki; Siti Rohaya (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
In overcoming the problems of economic, many rural communities in Gunung Kidul Regency have switched to developing natural asset-based village tourism. The village tourism management is mostly carried out through BUMDes. The problem of developing rural tourism is the problem of tourism promotion, where the process of promoting village tourism tends to be carried out separately, especially through online promotion. It has an impact on tourists who are not easy to find tourist destination maps of villages in Gunung Kidul Regency. This study uses a combination of asset-based approach and integrated information system as an effort to provide a way out to promote the exoticism of natural assets such as beaches, hills, caves, culinary and other assets to be more explored and more heavily promoted among tourists. As a result, tourism promotion which was originally carried out separately has now been integrated, so that a new spirit is created for tourists to visit these tourist sites. The integrated information system makes easier for tourists to see the map and the beautiful charm of a tourist village in Gunung Kidul, Yogyakarta.